2019
DOI: 10.1002/andp.201900201
|View full text |Cite
|
Sign up to set email alerts
|

The Linear Optical Unambiguous Discrimination of Hyperentangled Bell States Assisted by Time Bin

Abstract: A linear optical unambiguous discrimination of hyperentangled Bell states is proposed for two-photon systems entangled in both the polarization and momentum degrees of freedom (DOFs) assisted by time bin. This unambiguous discrimination scheme can completely identify 16 orthogonal hyperentangled Bell states using only linear optical elements, where the function of the auxiliary entangled Bell state is replaced by time bin. Moreover, the possibility of extending this scheme for distinguishing hyperentangled Bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…In our scheme, the 16 hyper-Bell states are distinguished unambiguously. One fixed momentum (spatial) entangled state and one time-bin DOF are employed by Gao et al [44] to complete momentum-(spatial-) polarization HBSA. One fixed momentum (spatial) entangled state and one fixed frequency entangled state are employed by Wang et al [56] to complete momentum-(spatial-) polarization HBSA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our scheme, the 16 hyper-Bell states are distinguished unambiguously. One fixed momentum (spatial) entangled state and one time-bin DOF are employed by Gao et al [44] to complete momentum-(spatial-) polarization HBSA. One fixed momentum (spatial) entangled state and one fixed frequency entangled state are employed by Wang et al [56] to complete momentum-(spatial-) polarization HBSA.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Li et al [43] showed that 4 n hyper-Bell states can be separated into 2 n+k+1 −2 2k distinct groups via linear optics with help of k (k ≤ n) additional entangled states in ancillary DOFs. In 2019, Gao et al [44] proved that 2 n+k+1 hyper-Bell states in n (n ≥ 2) DOFs can be distinguished via linear optics with help of a time delay and k (k ≤ n) auxiliary entangled states in additional DOFs. In 2020, Gao et al [45] further enhanced to 14 distinct groups only assisted by time-bin DOF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[37] Tremendous progress has also been made in hyperentangled Bell states analysis (HBSA). [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] In 2007, Wei et al [48] shown that 16 hyperentangled Bell (hyper-Bell) states cannot be unambiguously distinguished only using linear optics. Later, the first complete HBSA scheme was proposed by Sheng et al [49] in 2010 via cross-Kerr nonlinearity, and another interesting HBSAs via cross-Kerr nonlinearity were proposed later.…”
Section: Introductionmentioning
confidence: 99%
“…Tremendous progress has also been made in hyperentangled Bell states analysis (HBSA). [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] In 2007, Wei et al [48] shown that 16 hyperentangled Bell (hyper-Bell) states can not be unambiguously distinguished only using linear optics. Later, the first complete HBSA scheme was proposed by Sheng et al [49] in 2010 via cross-Kerr nonlinearity, and another interesting HBSAs via cross-Kerr nonlinearity were proposed later.…”
Section: Introductionmentioning
confidence: 99%